2022
DOI: 10.4143/crt.2020.1106
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Exposure to Pesticides and Lung Cancer Risk: A Propensity Score Analyses

Abstract: Occupational exposure to pesticides is thought to be associated with lung cancer, but studies have yielded conflicting results. We performed a propensity score (PS) based analyses to evaluate the relationship between occupational exposure to pesticides and lung cancer risk in the Korea National Cancer Center community-based cohort study (KNCCCS). Materials and MethodsDuring the follow-up period, 123 incidental lung cancer cases were identified, of the 7,471 subjects in the final statistical analysis. Informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Recent findings from systematic reviews and exposure epidemiology studies confirmed this association: Kim et al, by evaluating 7471 subjects, found an HR of 1.82 (95% CI: 1.11-2.98) between LC and occupational pesticide exposure, with a higher rate among men. These data have been also confirmed by considering different propensity score matching (PSM) methods, thus reinforcing the statistical significance of the analysis [137].…”
Section: Pesticidesmentioning
confidence: 59%
“…Recent findings from systematic reviews and exposure epidemiology studies confirmed this association: Kim et al, by evaluating 7471 subjects, found an HR of 1.82 (95% CI: 1.11-2.98) between LC and occupational pesticide exposure, with a higher rate among men. These data have been also confirmed by considering different propensity score matching (PSM) methods, thus reinforcing the statistical significance of the analysis [137].…”
Section: Pesticidesmentioning
confidence: 59%
“…Moreover, our findings were in line with previous studies that showed that workers in the agriculture industry were related to a high risk of lung cancer [ 37 , 38 ]. Occupational exposure to pesticides has been pointed out as the main causes of high lung cancer incidences among agriculture workers [ 37 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most OPPs feature a phosphorothioate group (P = S), which is safer than those with the P = O linkage because it has less reactivity with biomolecules and is hydrolytically stable [ 272 ]. Although many studies have identified the link between exposure to OPPs and the risk of LC, the precise carcinogenesis of these compounds is not yet well known [ 270 , 273 , 274 , 275 ]. A prospective study that was a component of the Agricultural Health Study (AHS) offered more proof in favor of a connection between lung cancer risk and pesticide use [ 274 ].…”
Section: Environmental Toxicants and Lung Cancermentioning
confidence: 99%